Insights into TtCIPK gene family and its roles in durum wheat in response to PEG and ABA treatments - Hadiseh Sadat Hosseini Pouya; Monireh Cheniany; Parviz Heidari (Scientific Reports)
Abstract Drought is one of the significant abiotic stresses seriously affecting plant growth and productivity. In this regard, the identification and utilization of genetic factors improving mechanisms of drought tolerance should be of primary importance. Calcineurin B-like interacting protein kinases (CIPKs) are crucial regulators in calcium signaling pathways, mediating plant responses to abiotic stresses. The present study includes the first comprehensive analysis of the CIPK gene family in durum wheat. A total of 58 TtCIPKs were identified using bioinformatics prediction and then classified into six evolutionary groups by the phylogenetic analysis. Results from the structural analysis indicated variations in exon–intron organizations; members segregated into high- and low-exon-number subgroups. Predictions of subcellular localization indicated that most TtCIPKs are located in the chloroplast and cytosol. According to qPCR results, TtCIPK genes exhibited tissue-specific expression. Besides, it was stated that TtCIPK genes are induced in response to drought stress by both ABA-dependent and independent signaling pathways. Further, phosphorylation site predictions and conserved domain analyses showed functional diversity among TtCIPKs, supporting their roles in stress adaptation. These findings are important for understanding the molecular mechanism of drought tolerance in durum wheat and lay the foundation for developing stress-resilient wheat varieties. The findings provide new insights into ABA-mediated and independent pathways in durum wheat’s drought response. These insights lay a foundation for leveraging CIPK genes in developing drought-tolerant wheat varieties, addressing a critical challenge in sustainable agriculture.